2017
DOI: 10.1021/acs.inorgchem.7b02013
|View full text |Cite
|
Sign up to set email alerts
|

Blue Fluorescence from BF2 Complexes of N,O-Benzamide Ligands: Synthesis, Structure, and Photophysical Properties

Abstract: Small molecules having intense luminescence properties are required to promote biological and organic material applications. We prepared five types of benzamides having pyridine, pyridazine, pyrazine, and pyrimidine rings and successfully converted them into three types of the difluoroboronated complexes, Py@BAs, as novel blue fluorophores. Py@BA having a pyridine moiety (2-Py@BA) showed no fluorescence in solution, whereas Py@BAs of pyridazine and pyrazine moieties (2,3-Py@BA and 2,5-Py@BA, respectively) emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…One of the least studied classes of the N,O-coordinating organoboron dyes is based on the oxadiazaborinine ring . Usually, the oxadiazaborinine dyes have been synthesized by complexation of boron trifluoride with amide of electron-poor 2-amino- N -heterocycles such as pyridine, pyrazine, , pyridazine, 1,8-naphthyridine, or 1,3,4-thiadiazole . Our conception is based on the incorporation of an electron-rich heterocyclic building block into the oxadiazaborinine structure to increase the chemical stability of these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the least studied classes of the N,O-coordinating organoboron dyes is based on the oxadiazaborinine ring . Usually, the oxadiazaborinine dyes have been synthesized by complexation of boron trifluoride with amide of electron-poor 2-amino- N -heterocycles such as pyridine, pyrazine, , pyridazine, 1,8-naphthyridine, or 1,3,4-thiadiazole . Our conception is based on the incorporation of an electron-rich heterocyclic building block into the oxadiazaborinine structure to increase the chemical stability of these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is only one previous publication addressing the influence of the nitrogen atom position in isoelectronic BF 2 derivatives on properties of dyes. 32 However, that contribution considered three (out of five) nitrogen positions and, more importantly, those molecules were not photoisomerizable.…”
mentioning
confidence: 99%
“…Moreover, the successful functionalization of BF-carrying compounds to optimize their photochemical properties has been regularly achieved, through substitution, extension of the conjugated path with either double or triple carbon–carbon bonds, planarization, benzoannulation, substitution of the fluorine atoms, replacement of an atom binding Lewis acid, etc. 16 , 17 Recently, Yamaji et al demonstrated that the fluorescence quantum yield in two diazine-based difluoroborates significantly differ from that of the corresponding pyridine derivative, 18 , 19 and we decided to adopt a similar strategy in our research to enhance fluorescence quantum yield, thus maximizing TPACS.…”
mentioning
confidence: 99%
See 2 more Smart Citations